Hybrid discursive formations – a case study of an investigative commission meeting transcripts - Rzeszutko, Małgorzata (Papers in Linguistics, 2020)
The aim of the article is to show that utterances appearing during an investigative commission’s work constitute a contamination of the generic features of interviews and court hearings, and therefore present a new type of hybrid discursive formations. The examined utterances function in the public space both in its institutional as well as mass dimensions. The fact that the activities of an investigative commission are based on the code order (an oath, citing points and paragraphs of the code, etc.) evokes jurisdictional contexts. On the other hand, extralinguistic determinants such as recording, presence of television crews, live broadcasting, the character of participants (important people from the world of politics, public life), as well as certain linguistic features, e.g. freedom of expression, the way of asking questions and answering them, refer to the poetics of the interview. Standardized forms of interaction (formulas, petrified phrases) coexist with self-promotional statements typical of interviews. The analysed material represents a contemporary postmodern discourse, characterized by dynamics, provocation, creativity, openness, “mixing” genres, blurring the boundaries between the public and the private space. The multisemiotic character, modification of the classic system of role distribution with a sender and a receiver, increased persuasiveness and interactivity of the message all point to the discursive and social change that is taking place. Utterances which appear as part of investigative commission’s meetings are characterized by jurisdictional procedural embedment and the occurrence of theatrical addition and show typical of the media. The constitute a genre contamination, a hybrid discursive formation.